Adjunct prednisone therapy for patients with community-acquired pneumonia: a multicentre, double-blind, randomised, placebo-controlled trial. Issue 9977 (18th April 2015) - Blum, Claudine Angela; Nigro, Nicole; Briel, Matthias; Schuetz, Philipp; Ullmer, Elke; Suter-Widmer, Isabelle; Winzeler, Bettina; Bingisser, Roland; Elsaesser, Hanno; Drozdov, Daniel; Arici, Birsen; Urwyler, Sandrine Andrea; et al.
Summary: Background: Clinical trials yielded conflicting data about the benefit of adding systemic corticosteroids for treatment of community-acquired pneumonia. We assessed whether short-term corticosteroid treatment reduces time to clinical stability in patients admitted to hospital for community-acquired pneumonia. Methods: In this double-blind, multicentre, randomised, placebo-controlled trial, we recruited patients aged 18 years or older with community-acquired pneumonia from seven tertiary care hospitals in Switzerland within 24 h of presentation. Patients were randomly assigned (1:1 ratio) to receive either prednisone 50 mg daily for 7 days or placebo. The computer-generated randomisation was done with variable block sizes of four to six and stratified by study centre. The primary endpoint was time to clinical stability defined as time (days) until stable vital signs for at least 24 h, and analysed by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00973154 . Findings: From Dec 1, 2009, to May 21, 2014, of 2911 patients assessed for eligibility, 785 patients were randomly assigned to either the prednisone group (n=392) or the placebo group (n=393). Median time to clinical stability was shorter in the prednisone group (3·0 days, IQR 2·5–3·4) than in the placebo group (4·4 days, 4·0–5·0; hazard ratio [HR] 1·33, 95% CI 1·15–1·50, p<0·0001). Pneumonia-associated complications until day 30 did not differ between groups (11 [3%] in the prednisone group and 22 [6%] in the placebo group; odds ratio [OR] 0·49 [95% CI 0·23–1·02]; p=0·056). The prednisone group had a higher incidence of in-hospital hyperglycaemia needing insulin treatment (76 [19%] vs 43 [11%]; OR 1·96, 95% CI 1·31–2·93, p=0·0010). Other adverse events compatible with corticosteroid use were rare and similar in both groups. Interpretation: Prednisone treatment for 7 days in patients with community-acquired pneumonia admitted to hospital shortens time to clinical stability without an increase in complications. This finding is relevant from a patient perspective and an important determinant of hospital costs and efficiency. Funding: Swiss National Science Foundation, Viollier AG, Nora van Meeuwen Haefliger Stiftung, Julia und Gottfried Bangerter-Rhyner Stiftung.